Examining the influence of two emotion regulation strategies on anxiety in Chinese college students: insights from cross-lagged and moderated network models - Xinyuan Zou; Yichao Lv; Qihui Tang; Shujian Wang; Xinze Liu; Liang Zhang; Yanqiang Tao; Jingyi Zhou (BMC Psychology)
Abstract Background Anxiety, a prevalent and detrimental mental disorder, usually emerges in late adolescence and emerging adulthood. Emotion regulation strategies, namely expressive suppression and cognitive reappraisal, share a close relation with the onset and maintenance of anxiety. Yet the relation between anxiety and emotion regulation strategies remains controversial and warrants further clarification. Methods The generalized anxiety disorder-7 (GAD-7) was used to measure the anxiety disorders and the emotion regulation questionnaire (ERQ) was utilized to assess the use of two emotion regulation strategies. In study 1, a total of 2201 college students completed two measurement waves (females = 1358, 61.70%, Mage = 18.37). The cross-lagged model was conducted to identify the directional relation between two emotion regulation strategies and anxiety. In study 2, 3150 college students (females = 1562, 49.59%, Mage = 19.73) completed the measurements. The moderated network model was utilized to clarify the influence of emotion regulation strategy on anxiety from the symptomatic perspective. Results In study 1, the results of the cross-lagged model suggested that the level of anxiety in wave 2 could be negatively predicted by the cognitive reappraisal (b = −0.552, p < .01) but not by expressive suppression (b = 0.035, p = .174) in wave 1. In study 2, the results of the moderated network indicated that cognitive reappraisal could moderate the interaction between “Excessive worry”-“Irritability”, “Nervousness” -“Uncontrollable worry”, “Trouble relaxing”-“Nervousness” (GAD1) ,and “Restlessness” -“Irritability”. Conclusions The current study confirmed cognitive reappraisal could serve as a protective factor for anxiety by diminishing the positive relation between “Excessive worry”-“Irritability” and “Nervousness” -“Uncontrollable worry”. This finding may guide clinical workers to develop more targeted interventions using cognitive reappraisal to alleviate anxiety symptoms.